On Catalan's Conjecture - Huovinen, Risto (My University, 2024)
Catalan's conjecture states that there are no solutions in natural numbers to Catalan's equation x^n-y^m=1, where x,y>0 and n,m>1, except 3^2-2^3=1. In this work we present partial results related to Catalan's conjecture without proving the conjecture itself. We show that if (x,y,n,m) is a solution to Catalan's equation and y is a prime number, then y=2, x=3, n=2, and m=3. We prove Cassels' Theorem, which gives divisibility condition for such solutions (x,y,n,m) to the Catalan's equation, where n and m are odd primes. Using Cassels' Theorem, we prove further divisibility conditions for such solutions (x,y,n,m) to the Catalan's equation, where n and m are odd primes. We employ theory of cyclotomic fields to prove Inkeri's Theorem, which we use to show that the equation x^p-y^q=1, where p,q are odd primes, has no solutions x,y>0 for a large number of primes p,q.

Catalanin otaksuma on väittämä, jonka mukaan Catalanin yhtälöön xn − ym = 1, missä x, y > 0 ja n, m > 1 ovat luonnollisia lukuja, ei ole muita ratkaisuja kuin 32 − 23 = 1. Tässä työssä tarkastellaan Catalanin otaksumaan liittyviä osittaisia tuloksia. Catalanin otaksuma esitetään, mutta sitä ei todisteta. Tutkielmassa todistetaan, että jos Catalanin yhtälön ratkaisussa (x, y, n, m) y on alkuluku, niin y = 2 ja x = 3, n = 2, m = 3. Lisäksi todistetaan Casselsin lause, mikä antaa jaollisuusehtoja sellaisille Catalanin yhtälön ratkaisuille (x, y, n, m), missä n ja m ovat parittomia alkulukuja. Casselsin lauseen avulla todistetaan lisää jaollisuusehtoja sellaisille Catalanin yhtälön ratkaisuille (x, y, n, m), missä n ja m ovat parittomia alkulukuja. Tutkielman lopussa esitetään tuloksia ympyräkunnista ja niiden ihanteista ja todistetaan Inkerin lause, minkä avulla todistetaan, että suurelle määrälle alkulukuja p, q > 2 yhtälölle xp − yq = 1 ei ole ratkaisuja, missä x, y > 0.
Keywords: Catalan's conjecture, Cyclotomic field, Catalanin otaksuma, ympyräkunta